The Effect Of Service Quality, Price, And Promotion On Glass Sales At PT. Prisma Danta Abadi Batam - Peuhulu , Werenfridus Gulevear; Nuraeni , Brigida Endah; Junianto , Pilifus (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This study aims to determine the influence of service quality, price, and promotion on the sales of glass at PT Prisma Danta Abadi Batam. The data collection techniques employed in this research include literature review and the distribution of questionnaires. This research utilizes a quantitative research method. The sample size determination in this study uses purposive sampling with a total of 50 respondents. The result of the study with a significance level of 5% indicate that: (1) The variable of service quality has a positive and significant effect on glass sales, this can be seen from a significant value of 0,047 smaller than 0,05 and 2,039 > 2,010. (2) The variable of price has a positive and significant effect on glass sales, this can be seen from a significant value of 0,047 smaller than 0,05 and 2,039 > 2,010. (3) The variable of promotion has a positive and significant effect on glass sales, this can be seen from a significant value of 0,009 smaller than 0,05 and 2,733 > 2,010. (4) The Variabel of service quality, price, and promotion together affect glass sales by 45,8% and the remaining 54,2% is influenced by another factor outside the research variable used, this shows that the calculated is 12,962 > 2,798 with significance of 0,000 Keywords: Effect of Service Quality, Price and Promotion on glass Sales of PT Prisma Danta Abadi Batam